A Robust and Flexible Control System to Reduce Environmental Effects of Thermal Power Plants - Eguchi, Toru; Sekiai, Takaaki; Kusumi, Naohiro; Yamada, Akihiro; Shimizu, Satoru; Fukai, Masayuki (IntechOpen, 2011)
None